The Relationship between High School Teachers' Organizational Support Perceptions and Their Organizational Cynicism Attitudes - Gokyer, Necmi; Turkoglu, Ismail (Turkish Education Assoc, 2018)
The objective of this research study is to determine the relationship between perceptions of organizational support and attitudes of organizational cynicism in teachers who work in high schools. The relational screening model among the general screening models was recruited in this research study. The universe of the study constitutes a total of 2805 teachers from different branches working in 47 high schools in Elazig province during 2016-2017 academic year. According to the results of the research; perceptions of the teachers' organizational support and justice sub-dimension are in the level of high, while the teachers' perceptions of the personal and professional development sub-dimension and the whole scale are in moderate level. The teachers' perceptions of the organizational ownership sub-dimension is in the level of low. There is a high level of relationship between organizational support and justice and personal and professional development. For gender change, female teachers' perceptions of organizational ownership are more positive than male teachers. The perceptions of the teachers working in the province center on the scale and organizational support and justice and personal and professional development sub-dimensions arc higher than the district centers. As for the question of 'do you think that they will leave the institution?', 64% of the teachers answered no, 18,4% responded as partially and 17,6% responded yes. The highest score that teachers receive from organizational cynicism is the cognitive cynicism attitude scores. There is a moderately negative correlation between cognitive and affective cynicism and organizational support and justice: and there is a weak negative relationship between behavioral cynicism and organizational support and justice. Together with organizational support and justice, personal and professional development and organizational ownership subfactors present a moderate, negative and meaningful relationship with teachers' cognitive cynicism attitude scores.
Keywords: High school; Teacher; Perception of organizational support; Organizational cynicism; Cynicism